Mobile Learning with STEM Approach in Physics Learning - Asmiliyah, Asmiliyah; Khaerudin, Khaerudin; Solihatin, Etin (Journal of Education Reseach and Evaluation, 2021)
Most of the physics done in schools is more about learning on knowledge and understanding of the material, without developing problem-solving skills and applying concepts in real-life contexts. Students still often use the plug & chug and memory-based approach in solving physical problems. It causes students to be able to solve simple quantitative issues but cannot solve more complex issues. This study aims to produce mobile learning with a feasible and practical STEM approach for physics lessons. This research is a Research and Development (R&D) using the Alessi and Trollip model. The model consists of three stages of development, namely planning, design, and development. The methods used to collect data are interviews and questionnaires. The instrument used to collect data is a questionnaire. The technique used to analyze the information is descriptive qualitative and quantitative analysis. Based on trials conducted by learning design experts, media experts, and materials experts and direct effectiveness tests using products with tangible goals. It was found that mobile learning applications with a STEM approach were feasible and effective in physical learning. Combining STEM approaches and problem-based learning models with mobile learning can be one of the suitable lessons for making. This study indicates that the development of cross-platform mobile learning applications with a STEM approach is feasible and effective in learning physics.